Sun song - Marzollo, Jean.; Regan, Laura (New York, NY : HarperCollins, 1995)
Animals and plants respond to the sun$1 (Bs changing light over the course of a single day.s
Keywords: Day -- Fiction; Stories in rhyme; Sun -- Fiction